Manajemen Literatur untuk Koleksi Digital: Studi Akuisisi dan Organisasi Informasi Pada Perpustakaan Universitas Muhammadiyah Surakarta - Imelda Wigati; Mega Alif Marintan (Perpustakaan Universitas Riau, 2025)
This study aims to analyze the implementation of literature management in the management of digital collections at the Muhammadiyah University of Surakarta (UMS) Library to support effective information retrieval. A qualitative descriptive method was employed through documentation study, metadata analysis, and observation of digital systems, including Koha, the institutional repository, and the integrated search portal FIND@UMSLi. The findings indicate that digital collection management at the UMS Library refers to the guidelines of the International Federation of Library Associations and Institutions (IFLA), particularly in acquisition and information organization. The application of the Dublin Core metadata standard, combined manual and automated indexing, and integrated search systems contribute to improved organization and accessibility of digital collections. However, several challenges were identified, including limited funding, inconsistent metadata quality, delays in accessing scholarly articles, and limited technological competencies among librarians. These findings suggest that standardized literature management plays a crucial role in enhancing the quality and sustainability of digital library services. Strengthening institutional policies, upgrading technological infrastructure, and improving librarians’ digital competencies are necessary to optimize digital collection management.